Effect of off-pump coronary artery bypass surgery on clinical, angiographic, neurocognitive, and quality of life outcomes: randomised controlled trial. Issue 7554 (1st June 2006) - Al-Ruzzeh, Sharif; George, Shane; Bustami, Mahmoud; Wray, Jo; Ilsley, Charles; Athanasiou, Thanos; Amrani, Mohamed
Abstract: Objective To compare the clinical, angiographic, neurocognitive, and quality of life outcomes of off-pump coronary artery bypass surgery with conventional coronary artery bypass grafting surgery using cardiopulmonary bypass. Design Randomised controlled clinical trial. Setting Tertiary cardiothoracic centre in Middlesex, England. Participants 168 patients (27 women) requiring primary isolated coronary artery bypass grafting surgery. Interventions Patients were randomised to conventional coronary artery bypass grafting surgery using cardiopulmonary bypass (n = 84) or off-pump coronary artery bypass surgery (n = 84), carried out by one surgeon. Angiographic examination was carried out at three months postoperatively. Neurocognitive tests were carried out at baseline and at six weeks and six months postoperatively. Main outcome measures Clinical outcome, graft patency at three months, neurocognitive function at six weeks and six months, and health related quality of life. Results Graft patency was evaluated by angiography in 151 (89.9%) patients and was similar between the cardiopulmonary bypass and off-pump groups (risk difference − 1%, 95% confidence interval − 5% to 4%), with the off-pump group considered the treatment group. Patients in the off-pump group required fewer blood transfusions (1.7 units v 1.0 unit, P = 0.02), shorter duration of mechanical ventilation (7.7 hours v 3.9 hours, P = 0.03), and shorter hospital stay (10.8 days v 8.9 days). Scores for neurocognitive function showed a significant difference in three memory subtests at six weeks and two memory subtests at six months in favour of the off-pump group. Conclusions Patients who underwent off-pump coronary artery bypass surgery showed similar patency of grafts, better clinical outcome, shorter hospital stay, and better neurocognitive function than patients who underwent conventional coronary artery bypass grafting surgery using cardiopulmonary bypass.